Bats at the end of the world: new distributional data and fossil record from Patagonia, Argentina - Udrizar Sauthier, Daniel Edgardo (2013)
We report new recent and fossil records in Patagonia for six and three bat species, respectively. These findings significantly increase the previously known number of localities for these mammals in this entire region, filling gaps between previous references for some species (e.g., Histiotus macrotus) and/or extending by 140–350 km the range of others (e.g., Myotis chiloensis, M. levis, Lasiurus varius). In addition, we report for the second time the vespertilionid bat Lasiurus blossevillii in Patagonia. Fossils are mostly restricted to the Late Holocene epoch, and the recorded assemblages are similar to the recent ones. A preliminary analysis of richness indicates that bat diversity south of the Colorado River (around 39°S) decreases from five to six species in the northwestern to one species in the southeastern, changing abruptly around 43°S–46°S. Compared with similar latitudes of the Northern Hemisphere, bat diversity in the Neotropics follows a similar pattern, with <20 taxa occurring south of 35°S.